OCUPATIONAL STRESS IN TEACHERS OF METROPOLITAN LIMA AND ITS RELATION WITH PERSONAL, PROFESSIONAL AND INFRASTRUCTURE AND EDUCATIONAL RESOURCES FACTORS - Palacios Jimenez, Alberto Salvador (2020)
Objectives: To analyze the relationship between the work stress of teachers in Metropolitan Lima with personal and professional factors and the perception of the quality of infrastructure and educational resources. Materials and methods: The study is non-experimental, descriptive and quantitative. The sample is made up of 130 teachers from Metropolitan Lima. The instruments to be used is the Maslach Burnout Inventory for educators, which consists of personal and professional characteristics, and the questionnaire, which deals with the perception of the quality of infrastructure and educational resources. Results: It was determined that there is no relationship between stress levels and sex (p = 0.139) or age groups (p = 0.164). Regarding professional factors, academic degree (p = 0.017), years of experience (p = 0.036) and length of stay in the same institution (p = 0.018) are related to work stress. The conditions of school infrastructure (p = 0.056) and the preparation of support staff (p = 0.232) are not related to work stress, unlike access to resources for the development of learning, a factor that is related to work stress (p = 0.002). Conclusions: Work stress is not related to personal factors. Work stress has a significant relationship with professional factors. Work stress is related to the perception of the quality of resources for learning.